[Speakers hand in hand at Multicultural Center dedication], January 15, 1982 (1982)
Speakers standing hand-in-hand in University Union plaza. People photographed include ASI president Dennis Hawk, Professor David Sanchez, San Luis Obispo Mayor Melanie Billig, Professor Quintard Taylor, and Cal Poly President Warren Baker.